Early feeding after free flap reconstruction for oral cancer. Issue 7 (September 2015) - McAuley, D.; Barry, T.; McConnell, K.; Smith, J.; Stenhouse, J.
Abstract Traditionally, after resection of oral cancer and free flap reconstruction, patients are given nothing by mouth for between 6 and 12 days to allow adequate time for healing and to reduce the risk of dehiscence. To assess the impact of early oral feeding after operation we retrospectively reviewed 10 consecutive patients who had had surgical resection and free flap reconstruction for oral cancer. Details recorded included histopathological findings, stage and site of the primary tumour, and type of reconstruction. Data on the duration of tracheostomy, commencement of clear fluids and diet, complications, and duration of hospital stay, were also recorded. Half of the patients were able to tolerate clear fluids orally by the first postoperatively day and the remaining half by the second. By the fourth day, 8 could manage a pureed diet. There were no complications. A mean duration of hospital stay of 11 days (range 5–16) compared favourably with previous studies. Early oral feeding was not associated with any increased morbidity or adverse outcome. A shorter hospital stay may favour the adoption of an improved recovery programme as seen in other surgical specialties.